IMPROVING THE MOVEMENT QUALITY „SPEED” IN SECONDARY SCHOOL THROUGH THE AGENCY OF THE MOVEMENT GAMES - Cristian ŞANTA; Corneliu ROŞ; Onela ŞANTA (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2016)
The importance of physical education and implicitly of the development of the movement qualities in the general process of instruction and education of pupils is revealed by the fact that it represents the only subject in the curriculum which mainly has the role of acting in the field of development and physical preparation of establishing and realizing a corresponding equilibrium between the intellectual and physical effort – an element of great importance in the normal growing and developing of pupils. Starting from the premise that the secondary school pupils have a low level of the movement quality – speed, I come with the hypothesis that through acting with appropriate means and movement games on speed, it is a factor of progress in the amelioration of this, having as a result the improvement of the speed ratings, an important objective in the scholar physical education.